CUSTOMER RELATIONSHIP AND DORMITORY MANAGEMENT OF HOME DEANS: THEIR INFLUENCE ON STUDENTS’ QUALITY OF LIFE - de Ocampo, Lowena; Kae Azucena, Naomi; Baret, Marivec; Duterte, Jhon Marlo; Laranjo, Honeylyne Espedilla Concepcion; Niez, Nemcy (11th International Scholars Conference, 2016)
This study intends to determine the influence of customer relationship and management of the dormitory deans on the quality of life of students living in the dormitories in a certain private university. A total of 116 randomly selected students from five dormitories were the participants of this study. The majority of the respondents’ age ranged from 16-20 (59.5%), and 21-15 (32.8%) years old, females (48.3%), and with income below P10,000.00 (53.4%). The results of the study show that the customer relationship of the home deans with the students living in the dormitory was rated satisfactory. The dormitory management profile in terms of safety, facilities, and quality of programs/services were rated satisfactory. The students’ quality of life was very satisfactory for spiritual practices, satisfactory for academic practices and very satisfactory for character development. Further results revealed that the customer relationship and dormitory management were significantly related to the students’ quality of life in terms of dormitory management facilities, dormitory management program, and dormitory management safety. Implications on the role of dormitory home deans on the quality of life of students were determined in this study.